Adjuvant interferon-gamma immunotherapy in a patient with progressive cerebral Nocardia abscesses. (June 2017) - Leentjens, Jenneke; Gresnigt, Mark S.; van de Veerdonk, Frank L.; Kox, Matthijs; Kullberg, Bart Jan; Pickkers, Peter; Brouwer, Annemarie E.; Netea, Mihai G.
Highlights: Nocardiosis is a rare gram-positive bacterial infection caused by aerobic actinomycetes most commonly observed in patients with immune defects. Mortality remains high despite optimal antimicrobial treatment, especially in patients with multiple Nocardia lesions. The use of adjuvant immunotherapy with interferon-gamma as adjuvant salvage therapy could be considered. Summary: Despite advances in medical care, mortality due to cerebral Nocardia abscesses remains unacceptably high. The case of a typical immunocompromised patient, who deteriorated clinically despite optimal antimicrobial treatment, is reported here. Adjuvant immunotherapy with interferon-gamma resulted in partial restoration of the immune response and a corresponding clinical and radiographic recovery.